1887 Neb. Laws 502-03, ch. 50, §§ 54-55 - (:unkn) unknown (General Publisher, 1887)
It shall not be lawful for any body of men whatever, other than the regular organized volunteer militia of this state, and the troops of the United States to associate themselves together as a military company or organization, or to drill or to parade with arms in any city or town in this state without the license of the governor thereof which license may at any time be revoked
--
Keywords: MILITIAS